Optimizing genomic parental selection for categorical and continuous-categorical multi-trait mixtures - Villar-Hernandez, Bartolo de Jesús; Perez-Rodriguez, Paulino; Vitale, Paolo; Gerard, Guillermo S.; Montesinos-Lopez, Osval A.; Saint Pierre, Carolina; Crossa, José; Dreisigacker, Susanne (MDPI, 2024)
This study presents a novel approach for the optimization of genomic parental selection in breeding programs involving categorical and continuous-categorical multi-trait mixtures (CMs and CCMMs). Utilizing the Bayesian decision theory (BDT) and latent trait models within a multivariate normal distribution framework, we address the complexities of selecting new parental lines across ordinal and continuous traits for breeding. Our methodology enhances precision and flexibility in genetic selection, validated through extensive simulations. This unified approach presents significant potential for the advancement of genetic improvements in diverse breeding contexts, underscoring the importance of integrating both categorical and continuous traits in genomic selection frameworks.